Studi pengaruh pengoperasian soot blower terhadap energi panas yang diserap superheater pada unit 2 PLTU tenayan - Fadhlul Fajri; Rafil Arizona (Jurnal Teknik Mesin Indonesia, 2022)
This study aims to determine the of heat transfer absorbed by the high temperature superheater (HTS) and low temperature superheater (LTS) in boiler unit before and after the soot blower. This research uses 3 methods, namely, literature study, field observation, and interviews. The results of analysis show the heat transfer rate absorbed by the high temperature superheater (Q_HTS) increases after 1 hour soot blower, which is 72240 MJ/hour from (Q_HTS) 1 hour before soot blower, which is only 65434 MJ/hour, (Q_HTS) increases after 2 hours soot blower, namely 72575 MJ/hour from (Q_HTS) 2 hours before soot blower only 66886 MJ/hour and (Q_HTS) increased after 3 hours soot blower which is 73903 MJ/hour from (Q_HTS) 3 hours before soot blower only 69545 MJ/hour, then rate heat transfer absorbed by the low temperature superheater (Q_LTS) increased after 1 hour soot blower, which was 91797 MJ/hour from (Q_LTS) 1 hour before soot blower was only 89625 MJ/hour, (Q_LTS) increased after 2 hours soot blower being 92208 MJ/ hours from (Q_LTS) 2 hours before soot blower which was only 90267 MJ/hour and (Q_LTS) increased after 3 hours soot blower which was 92582 MJ/hour from (Q_LTS) 3 hours before soot blower only 90536 MJ/hour.